2016
DOI: 10.4274/tjh.2014.0312
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Tissue Factor Pathway Inhibitor in Sepsis Patients Receiving Prophylactic Enoxaparin

Abstract: Objective:Sepsis syndrome is usually accompanied by activation of blood coagulation mechanisms. Earlier studies found deficiencies of the 3 main natural anticoagulants, antithrombin, protein C, and protein S. However, none of these inhibitors block tissue factor, the prime trigger of coagulation during sepsis that is controlled specifically by the tissue factor pathway inhibitor (TFPI). The aim of this study was to characterize the fluctuations in the levels of natural anticoagulants, particularly TFPI, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…However, it is a marker for endothelial dysfunction, which would fit with a localized endothelial effect of COVID‐19 20 . TFPI was also significantly increased in COVID‐19 critical vs noncritical patients; TFPI usually is found on the endothelial surface and release could be triggered by sepsis though data are conflicting 21,22 . The elevated tPA may explain part of the component of increased D‐dimer seen within the patients, due to dysfunctional fibrinolysis, and can also be seen as marker of endothelial dysfunction 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is a marker for endothelial dysfunction, which would fit with a localized endothelial effect of COVID‐19 20 . TFPI was also significantly increased in COVID‐19 critical vs noncritical patients; TFPI usually is found on the endothelial surface and release could be triggered by sepsis though data are conflicting 21,22 . The elevated tPA may explain part of the component of increased D‐dimer seen within the patients, due to dysfunctional fibrinolysis, and can also be seen as marker of endothelial dysfunction 23 .…”
Section: Discussionmentioning
confidence: 99%
“…TFPI activity levels were decreased in animals subjected to either burn injury or sepsis alone, with even lower activity when combinatory insults occurred, this decrease was most pronounced at 24 h with a rebound to near normal TFPI activity at 72 h ( 76 ). In humans, TFPI levels are found to be increased in several disease states, including sepsis ( 98 , 99 ). However, interpretation of TFPI levels as a biomarker of coagulopathy can be misleading, given its various isoforms and distribution within the body, and varied methods of measurement ( 100 ).…”
Section: Forty-eight Hours and Beyond: Post Burn Shock Resuscitationmentioning
confidence: 99%
“…This finding is consistent with a prior study, where TFPI levels increases during sepsis. 28 An important clinical implication from our study is that when vascular injury occurs in an ECMO patient, thrombin generation may be delayed and protamine administration may not immediately reverse this abnormality. Donahue et al previously demonstrated a similar phenomenon in CPB patients where free TFPI levels and TFPI activity remained elevated after protamine administration and did not return to normal until 24 hours after heparin was given.…”
Section: Discussionmentioning
confidence: 82%